Effects of aluminium on Clarias gariepinus physiology, gills histology and cholinesterase in vivo and in vitro - Fadzil, Nadia Izati; Shukor, Mohd Yunus; Sabullah, Mohd Khalizan; Mohd Daud, Hassan; Zulkharnain, Azham; Ahmad, Siti Aqlima (Smith and Franklin Academic Publishing, 2019)
The gill is the site of acid-base balance, ionic regulation, gas exchange, and nitrogenous waste excretion by fish. The physiological, histopathological and enzymatic alterations from Clarias gariepinus gills were examined to assess the effects induced in gill tissues within 96 h exposure to waterborne Al 2 (SO 4 ) 3 with different concentrations (25 to 300 mg/L). The exposure of C. gariepinus to aluminium showed deleterious effects to normal fish behaviours and varying degrees of gill damage when visualised under inverted light microscopy (stained with haematoxylin-eosin), scanning electron microscopy and transmission electron microscopy. The mortality rate was observed increasing with increased Al concentration showing noticeably disrupted lamellae, irregular nucleus shape and increasing area of vacuolation in treated fish gills associated with Al 2 (SO 4 ) 3 exposure concentration. Furthermore, electron microscopic X-ray microanalysis of fish gills exposed to sublethal Al revealed Al accumulated on the surface of the gill lamella. Al toxicity also gave inhibitory effects on cholinesterase (ChE) extracted from the fish gills with 90.0% inhibition at 300 mg/L Al highest concentration exposure (in vivo), whereas the Al metal ion inhibited 50% of ChE activity at 4.12 mg/L (IC 50 ).